2019
DOI: 10.1155/2019/7870109
|View full text |Cite|
|
Sign up to set email alerts
|

Wingless-Type MMTV Integration Site Family Member 5a Is a Key Secreted Islet Stellate Cell-Derived Product that Regulates Islet Function

Abstract: Background. Emerging evidence suggests that T2DM is attributable to the dysfunction of β-cells and the activation of islet stellate cells (ISCs). The wingless-type MMTV integration site family member 5a (Wnt5a)/frizzled 5 (Fzd5) signalling pathway might take part in this process. Our study is aimed at defining the status of ISCs during β-cell insulin secretion homeostasis by determining the role of the Wnt5a protein in the regulation of insulin production. We examined the effects of the status of ISCs on β-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…The present clinical study also identified that Wnt5a was significantly downregulated in newly diagnosed type 2 diabetes mellitus patients. An in vitro study showed that Wnt5a could increase the level of insulin when ISCs are co-cultured with islet b-cells 41 . In the present study, we showed that Wnt5a, Fzd5, bcatenin, Ror2 and P-CamKII were expressed in ISCs, albeit at a relatively high level under normoglycemic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The present clinical study also identified that Wnt5a was significantly downregulated in newly diagnosed type 2 diabetes mellitus patients. An in vitro study showed that Wnt5a could increase the level of insulin when ISCs are co-cultured with islet b-cells 41 . In the present study, we showed that Wnt5a, Fzd5, bcatenin, Ror2 and P-CamKII were expressed in ISCs, albeit at a relatively high level under normoglycemic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the Wnt5a protein expression in pancreatic samples (from 8, 20, and 28-weekold mice), immunohistochemistry was performed as described previously [7]. Mouse pancreases were fixed in 4% paraformaldehyde in 0.1M PBS for 24 h at 4°C, embedded in paraffin, and sectioned.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…, Insulin, Glucagon, and Desmin. Immunofluorescence microscopy was performed as described previously [7] to evaluate the expression of Wnt5a and its receptor Frizzled5 (Fzd5) in Min6 cells, and insulin, glucagon, and desmin in islets. Immunostaining was performed with polyclonal antibodies specific for Wnt5a, Fzd5, insulin, glucagon, and desmin (1 : 200, Abcam, Cambridge, UK).…”
Section: Immunofluorescence Microscopy Of Wnt5a Frizzled5mentioning
confidence: 99%
See 2 more Smart Citations